Application of EEG in migraine - Zhang, Ning; Pan, Yonghui; Chen, Qihui; Zhai, Qingling; Liu, Ni; Huang, Yanan; Sun, Tingting; Lin, Yake; He, Linyuan; Hou, Yue; Yu, Qijun; Li, Hongyan; et al. (Frontiers in Human Neuroscience, 2023)
Migraine is a common disease of the nervous system that seriously affects the quality of life of patients and constitutes a growing global health crisis. However, many limitations and challenges exist in migraine research, including the unclear aetiology and the lack of specific biomarkers for diagnosis and treatment. Electroencephalography (EEG) is a neurophysiological technique for measuring brain activity. With the updating of data processing and analysis methods in recent years, EEG offers the possibility to explore altered brain functional patterns and brain network characteristics of migraines in depth. In this paper, we provide an overview of the methodology that can be applied to EEG data processing and analysis and a narrative review of EEG-based migraine-related research. To better understand the neural changes of migraine or to provide a new idea for the clinical diagnosis and treatment of migraine in the future, we discussed the study of EEG and evoked potential in migraine, compared the relevant research methods, and put forwards suggestions for future migraine EEG studies.